2018
DOI: 10.2174/1871520616666160817104529
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Toxicity of Paclitaxel Biopolymer Formulation

Abstract: Thus, the PBF as a prolong drug needs to correct its parameters for further drug formulation development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, paclitaxel has obvious toxicity. For example, it can cause bone marrow suppression and peripheral neuropathy ( 22 ). However, in a first-line study of non-small cell lung (NSCLC), nab-paclitaxel combined with carboplatin was used, and the results showed that the combination could reduce cytotoxicity ( 23 ).…”
Section: Paclitaxel Binding Domainmentioning
confidence: 99%
“…However, paclitaxel has obvious toxicity. For example, it can cause bone marrow suppression and peripheral neuropathy ( 22 ). However, in a first-line study of non-small cell lung (NSCLC), nab-paclitaxel combined with carboplatin was used, and the results showed that the combination could reduce cytotoxicity ( 23 ).…”
Section: Paclitaxel Binding Domainmentioning
confidence: 99%
“…and chemically synthesized polymers, PHB and its copolymers are obtained biotechnologically, which allows achieving a high degree of purity, setting and controlling the physicochemical properties of biopolymers within narrow limits in the process of their biosynthesis [1]. Because PHB has biodegradable and biocompatible properties simultaneously, it has received much attention as the base component for perspective medical devices [4][5][6][7] and drug dosage formulations [8][9][10][11][12][13] as well as novel friendly environment materials including packaging applications [14][15][16].…”
Section: Introductionmentioning
confidence: 99%